Collective Investment Decision Making with Heterogeneous Time Preferences - Christian Gollier; Richard Zeckhauser (Center for Economic Studies and ifo Institute (CESifo), 2003)
We examine the investment decision problem of a group whose members have heterogeneous time preferences. In particular, they have different discount factors for utility, possibly not exponential. We characterize the properties of efficient allocations of resources and of shadow prices that would decentralize such allocations. We show in particular that the term structure of interest rates is decreasing when all members have DARA preferences. Heterogeneous groups should not use exponential discounting for their collective investment decisions even if all agents discount exponentially.We also exhibit conditions that lead the representative agent to have a rate of impatience that decreases with GDP per capita.
Keywords: D70; 330; aggregation of preferences; hyperbolic discounting; impatience; time preference; investment and consumption